In search of the way thought and religion in early-modern Japan, 1582-1860 - Bowring, Richard 1947- (Oxford University Press, 2017)
This is a history of intellectual and religious developments in Japan during the Tokugawa period, covering the years 1582-1860. It begins with an explanation of the fate of Christianity, and proceeds to cover the changing nature of the relationship between Buddhism and secular authority, new developments in Shinto, and the growth of 'Japanese studies'. The main emphasis, however, is on the process by which Neo-Confucianism captured the imagination of the intellectual class and informed debate throughout the period. This process was expressed in terms of a never-ending search for the Way, a mode and pattern of existence that could provide not only order for society at large, but self-fulfilment for the individual. The narrative traces how ideas and attitudes changed through time, and is based on the premise that the Tokugawa period is important in and of itself, not merely as a backdrop to the Meiji Restoration of 1868
Keywords: Ideengeschichte 1582-1860; Geschichte 1582-1860; Geschichte; Philosophie; Religion; Religionsphilosophie; Japan; Philosophy / Japan / History; Japan / Religion / 1600-1868